PERKEMBANGAN POS KEADILAN PEDULI UMAT (PKPU) ACEH (2004 – 2016) - M. Yunus; Mawardi .; Anwar Yoesoef (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACTThis research raises the issue of how the Development of PKPU Aceh, 2004-2006. The purpose of this research is (1) to know the background of PKPU Aceh (2) the development of PKPU Aceh and (3) why PKPU still exist in Aceh after recontruski and rehabilitate Aceh. The data of this research are sourced from primary and secondary source, data collecting is done by four ways, that is literature study, observation, interview and documentation. The method used is descriptive and critical historical method with qualitative approach. The result of this research are (1) The Development of Aceh's Justice Peduli Peduli (PKPU) since 2004-2016 has brought changes to the social life of the people in Aceh. Especially the life of the poor / needy, orphans and the dhuafa. They are routinely trained through training, providing business capital, for orphans provided dormitory and free education to the level of higher education. (2) PKPU currently routinely manages humanitarian programs for the community from education, economy, health, emergency response, social and orphan. During 12 years of work in Aceh PKPU has become more widespread and global, showing real and professional work in humanitarian events in various places. and (3) Community's trust to PKPU is still very high, it is proven that the management of funds from the community both zakat, infak and alms as well as corporate CSR funds are entrusted the same PKPU. It is suggested that this research can benefit from what has happened. That is why the history of PKPU must also be written, hopefully can inspire various elements of society to continue to contribute and play an active role in tackling various natural disasters, social problems and humanitarian tragedy. Keyword: PKPU National Humanitarian Agency.